2011
DOI: 10.1177/147323001103900408
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ulinastatin on Postoperative Blood Loss in Patients Undergoing Open Heart Surgery with Cardiopulmonary Bypass

Abstract: This prospective, randomized, double-blind study evaluated the effect of ulinastatin on postoperative blood loss and transfusion requirements of patients undergoing open-heart surgery with cardiopulmonary bypass (CPB) and aortic cross-clamping (ACC). CPB and ACC produce variable systemic inflammatory reactions that are associated with multiorgan dysfunction via leucocytes, especially polymorphonuclear neutrophils (PMNs). PMNs increase blood loss and transfusion requirements. Ulinastatin, a urinary trypsin inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…The median sample size of the RCTs was 30 patients (range 15–60). With regard to the types of surgery, one trial assessed only aortic arch replacements [36], four trials only evaluated coronary artery bypass grafts (CABG) [23, 25, 29, 30], five trials reported only valve surgery [26, 28, 3335], three trials evaluated only repairs of atrial or ventricular septal defects [22, 24, 32], and two trails were mixed in nature [27, 31]. All trials except one [25] were conducted with CPB.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The median sample size of the RCTs was 30 patients (range 15–60). With regard to the types of surgery, one trial assessed only aortic arch replacements [36], four trials only evaluated coronary artery bypass grafts (CABG) [23, 25, 29, 30], five trials reported only valve surgery [26, 28, 3335], three trials evaluated only repairs of atrial or ventricular septal defects [22, 24, 32], and two trails were mixed in nature [27, 31]. All trials except one [25] were conducted with CPB.…”
Section: Resultsmentioning
confidence: 99%
“…Because all included studies were RCTs, the Jadad score for all studies was >2 with a mean overall Jadad score of 3.6 ± 1.1. Table 1 shows that twelve of the studies with a Jadad score > 3 were considered high-quality RCTs [20] and that four studies had a Jadad score = 5 [28, 29, 33, 35]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations